The Prevalence of Sports Betting in Tanzania Secondary School Students - Nuriath A. Habibu; Iramba F. Iramba; Yusuph Kambuga (Journal La Edusci, 2020)
The purpose of this paper was to determine the prevalence of sports betting among secondary school students in Tanzania. The study was conducted in the Dodoma region and covered four secondary schools in Dodoma City. The probability sampling procedure was used to select students randomly for everyone to have the chance of being involved. The judgmental sampling technique were used to collect information from the head of discipline units and class teachers, and simple random sampling was used to select both public and private secondary schools. The study administered questionnaires and interview questions to students, classes, head of discipline units, and class teachers. The questionnaires and interview questions targeted at picturing out the rate at which sports betting was intruding students. The finding shows that students aged between 10-17 years were reported to have high interest and feelings to take the risks of betting. The findings also show that females students are less involved in betting activities compared to male students. Besides, it was found that male students spend more of their precious time 6-10 hours a day in betting compared to female students. Furthermore, it was revealed that majority of students had taken part in more than one bet among the identified games including bet-way, premier bet, sport pesa, and tatu Mzuka.s